Commercial and Tactical Herbicides used in Vietnam and Thailand During the Vietnam War - Young, Alvin Lee (British Journal of Healthcare and Medical Research, 2025)
Issue: There continues to be much confusion among Vietnam and Vietnam-Era veterans, Non-Governmental Organizations, the Department of Defense, the Department of Veterans Affairs, and others as to the differences between the uses of military “tactical” herbicides versus the military use of “commercial” herbicides during the Vietnam War. If veterans were presumptively exposed to tactical herbicides while in military service in Vietnam, 9 January 1962 – 7 May 1975, they were entitled for health care for any of 19 different conditions “presumed to be service connected.” Health care and compensation were provided by the Agent Orange Act of 1991. Approximately 50,000 United States Air Force Veterans served at Royal Thai Airbases in the Kingdom of Thailand during the Vietnam War, especially during the years 1965-1971. Thailand veterans were previously eligible for health care for any injuries they incurred during their service. However, they were not eligible for conditions under the Agent Orange Act. Nevertheless, there have been numerous allegations that US Thailand veterans were indeed exposed to the wide-spread use of the same tactical herbicides, e.g. Agents Orange, White, and Blue, that had routinely been used in Vietnam to control unwanted vegetation. In 2022, the US Congress passed the PACT Act that permitted veterans who served in Thailand and Guam during the Vietnam War to be eligible for health care and compensation for 26 different conditions “presumed to be service connected” to their exposure to Agent Orange and other tactical herbicides while in service in Thailand during the period 9 January 1962 to 30 June 1976. The Congress made the decision despite the absence of any evidence from available historical records or the absence of any knowledge about the use of “commercial herbicides” during the Vietnam War. Thus, the issue is whether Thailand veterans were exposed to tactical herbicides or commercial herbicides and has that exposure impacted their long-term health. Background: The first use of tactical herbicides was on 7 January 1962 in Operation RANCHHAND in South Vietnam. Approximately 74.2 million L of Agents Orange, White and Blue were sprayed on jungles, mangroves, savannas and for crop denial. Records confirmed that limited quantities of tactical herbicides were stored in Thailand for missions by RANCH HAND in Laos. When Thailand joined the Allied Forces in the Vietnam War in September 1964, the Thai government, under the Rules of Engagement, did not permit tactical herbicides to be used for vegetation control on Royal Thai Airbases. If not tactical herbicides, could commercial herbicides be the explanation for Thailand veteran allegations? Tactical herbicides differed from commercial herbicides in the development and testing of formulations, purchase specifications, guidelines, regulatory oversight, shipment requirements, toxicological evaluations and military record keeping. Findings: Recently identified procurement records confirm that at least 262, 800 L of commercial low volatile 2,4-D and 2,4,5-T herbicides were shipped and approved for vegetation control on four airbases in Vietnam, 1962-1971. Records confirm that the total volume of low volatile 2,4,5-T shipped to Thailand was 29,120 L. Distribution to the Royal Thai Airbases and subsequent vegetation control was the responsibility of Pacific Architect & Engineers, a private company trained as commercial herbicide applicators for both Vietnam and Thailand. Dioxin (TCDD) analysis confirmed that the low volatile 2,4,5-T was ~ 1 ppm, and the rate of application, ~ 2.4 kg/ha, was similar to the same formulation sprayed in 1966 on 2.3 million ha on rangeland and pasture in the United States. It was also a choice herbicide for control of unwanted vegetation on most of the Department of Defense’s more 500 bases worldwide. Policy Considerations: The Congress of the United States, the Department of Veterans Affairs, and the Thailand Veterans simply refused to accept the reality that little or no exposure to either tactical or commercial herbicides or TCDD ever occurred on Royal Thai Airbases in Thailand. The dilemma for the DVA is that to recognize Thailand veterans for commercial herbicide exposure fails to acknowledge that millions of military men and women were on hundreds of military bases worldwide that were sprayed with the same low volatile 2,4-D and 2,4,5-T commercial herbicides from 1962 -1972.